2002
DOI: 10.1002/ana.10086
|View full text |Cite
|
Sign up to set email alerts
|

Parahippocampal tau pathology in healthy aging, mild cognitive impairment, and early Alzheimer's disease

Abstract: Abnormally phosphorylated tau accumulates as neurofibrillary tangles and neuropil threads in older persons with and without Alzheimer's disease. The relationship between neurofibrillary tangles and neuropil threads and how they relate to cognitive function is unknown. This study investigated the relationship between phosphorylated tau lesions and cognitive function in 31 persons participating in the Religious Orders Study, a prospective, longitudinal clinicopathological study of aging and Alzheimer's disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
150
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(166 citation statements)
references
References 45 publications
15
150
0
1
Order By: Relevance
“…Postmortem scores on AD-related pathologic indices for Braak staging, hippocampal NFTs, and diffuse and neuritic senile plaques were determined as described (47). The MMSE and NFT values were selected as our primary markers for quantifying AD progression because of the Braak scale's limited range and because our NFT results correlated more closely with the MMSE (r ϭ 0.45) than did our plaque values (r ϭ 0.19), consistent with prior findings (33)(34)(35)48). Further, the evidence that soluble rather than deposited A␤ may be more relevant to cognitive impairment is mounting (2,5,7).…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…Postmortem scores on AD-related pathologic indices for Braak staging, hippocampal NFTs, and diffuse and neuritic senile plaques were determined as described (47). The MMSE and NFT values were selected as our primary markers for quantifying AD progression because of the Braak scale's limited range and because our NFT results correlated more closely with the MMSE (r ϭ 0.45) than did our plaque values (r ϭ 0.19), consistent with prior findings (33)(34)(35)48). Further, the evidence that soluble rather than deposited A␤ may be more relevant to cognitive impairment is mounting (2,5,7).…”
Section: Methodssupporting
confidence: 72%
“…Based primarily on MMSE criteria (35,46), subjects were categorized initially into four groups, termed ''Control'' (MMSE Ͼ25), ''Incipient AD'' (MMSE 20-26), ''Moderate AD'' (MMSE [14][15][16][17][18][19], and ''Severe AD'' (MMSE Ͻ14) ( Table 1). Several borderline cases (e.g., MMSE ϭ 26) were assigned based on NFT, amyloid plaque, and Braak stage data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside the cell, the amyloid β (Aβ) peptide aggregates into clumps called oligomers, which accumulate and form deposits called amyloid plaques. Based on studies of a syndrome known as mild cognitive impairment (MCI) (a possible prodrome to dementia), the development of detectable entorhinal NFTs is considered to be the histological correlate of MCI and, many believe, the harbinger of incipient AD (1). Still, levels of cortical synaptic markers correlate with cognitive status at time of death better than do either plaque load or tangle load (2), which is consistent with the concept that neurotransmission failure is the proximate cause of cognitive decline.…”
Section: Sam Gandymentioning
confidence: 99%
“…In a triple transgenic mouse model, intraneuronal accumulation of Aβ was shown to be associated with deficits in synaptic plasticity before AD lesions developed. [33] Conversely, other autopsy studies [11,26,38] reported NFT to be the dominant lesion in AD and mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 97%